2017
DOI: 10.1097/bot.0000000000000746
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Patient-Initiated Telephone Calls After Orthopaedic Trauma Surgery

Abstract: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 16 publications
3
17
2
Order By: Relevance
“…Even patient phone calls, although often brief and and having the potential to increase patient satisfaction and decrease ED visits, can place a substantial burden on clinical staff. 6 The data from our study, however, did not support this idea that decreased narcotic prescriptions increases strain on medical resources.…”
Section: Discussioncontrasting
confidence: 80%
“…Even patient phone calls, although often brief and and having the potential to increase patient satisfaction and decrease ED visits, can place a substantial burden on clinical staff. 6 The data from our study, however, did not support this idea that decreased narcotic prescriptions increases strain on medical resources.…”
Section: Discussioncontrasting
confidence: 80%
“…A wound infection rate of 1·3 per cent was expected; most cases were superficial, although two patients had a deep wound infection. The surgery‐related visit rate to the hospital ED was 5·6 per cent, which is similar to or lower than rates reported in previous studies. The readmission rate of 1·9 per cent was also similar to that reported in previous studies, such as the rate reported in patients undergoing cholecystectomy within a 23‐h surgery model.…”
Section: Discussionsupporting
confidence: 85%
“…The sports subspecialty had the largest proportion of patients calling (16.9%), while foot and ankle had the lowest (4.0%); however, subspecialty was not shown to differ based on the chi-squared analysis. Though no evidence in the literature was found comparing call rates across subspecialties, Hadeed et al found that lower extremity procedures constituted the highest procedures for patient-initiated telephone calls during the first 14 days after discharge following orthopaedic trauma procedures [21].…”
Section: Discussionmentioning
confidence: 99%
“…A longer time would have potentially allowed for further assessment of this communication resource, but we felt patients were more likely to call within this given period and that this utilization rate would be similar if not decreased if the follow-up period was extended in duration. Previous studies have used similar follow-up periods [6,19,21]. There is also a likelihood that not all calls to the surgeon's personal number were recorded, as patients may not have left a voicemail or callback number if unable to directly reach the surgeon.…”
Section: Discussionmentioning
confidence: 99%